Participating in the Illness Journey: Meanings of Being a Close Relative to an Older Person Recovering from Hip Fracture-A Phenomenological Hermeneutical Study - Cecilia Segevall; Siv Söderberg (MDPI AG, 2022)
When an older person suffers an acute event, such as a hip fracture, it influences the whole family. Research shows that while close relatives want to be a part of the older person's life during recovery it is associated with a high perceived level of stress and burden. To provide in-depth knowledge of close relatives' experiences in this situation, the aim of this study was to elucidate meanings of being a close relative to an older person recovering from hip fracture surgery. This study has a qualitative descriptive phenomenological hermeneutical design. Narrative interviews were conducted with ten close relatives. Analysis was conducted using phenomenological hermeneutical interpretation which provided a deeper understanding of the close relatives' lived experiences of their older person's recovery from hip fracture surgery. The structural analysis revealed two themes; "Participating in the illness journey", which was constructed of the subthemes of facing the unimaginable yet expected, encountering healthcare personnel, and noticing recovery and "Putting oneself aside", which was constructed of the subthemes of placing daily life on hold, giving support, and feeling concern and fear.